An exploration of clinical reasoning and practices used by physiotherapists in the rehabilitation of horses following interspinous ligament desmotomy surgery. (3rd July 2022) - Sayers, Emma; Tabor, Gillian
ABSTRACT: Introduction: Clinical reasoning has not been studied in veterinary physiotherapy and so the methods used and factors involved are unknown. Similarly, the practices of veterinary physiotherapists within a certain rehabilitation programme have not been documented. The aim of this study was to explore the clinical reasoning and practices of veterinary physiotherapists during rehabilitation of horses following interspinous ligament desmotomy surgery. Methodology: A qualitative approach was taken and six members of the Association of Chartered Physiotherapists in Animal Therapy were interviewed using a semi-structured approach. The data were transcribed and analysed using Thematic Analysis. Results: Five themes were identified as relevant to the participants clinical reasoning. These related to structure of the assessment, modalities and reasoning of treatment, involvement of owner and veterinarian and the impact of comorbidities. The data highlight several different factors that influence clinical reasoning and decision making throughout the rehabilitation. An insight into practices involved is also documented. Conclusion: The process of clinical reasoning and decision making described appears complex. The input of both owner and veterinarian are evidently important and require the physiotherapists consideration. Decisions regarding assessment and treatment are influenced by many factors. A mixture of clinical experience and research evidence were used as support.